AB0493 COMPARISON OF EFFICACY AND SAFETY BETWEEN RITUXIMAB AND CYCLOPHOSPHAMIDE IN REMISSION INDUCTION THERAPY FOR JAPANESE ANCA-ASSOCIATED VASCULITIS(AAV) PATIENTS; A SINGLE CENTER RETROSPECTIVE ANALYSIS. (13th June 2020) - Kato, M.; Shimada, H.; Nakashima, S.; Mahmoud Fahmy Mansour, M.; Wakiya, R.; Miyagi, T.; Sugihara, K.; Ushio, Y.; Kameda, T.; Dobashi, H.
Abstract : Background: Rituximab(RTX) and Cyclophosphamide(CY) has been indicated for ANCA-associated vasculitis(AAV) as remission induction therapy. However, older age and renal disfunction were independent predictor of treatment related adverse effects in remission induction with CY in recent reports 1) . Japanese AAV patients are characterized by the predominance of elderly, and the study about comparison of efficacy and safety between RTX and CY in elderly Japanese AAV patients are limited. Objectives: To compare the efficacy and safety between RTX versus CY as remission induction therapy in Japanese AAV patients. Methods: We analyzed 40 cases (20 cases received RTX and 20 cases received CY) who received remission induction therapy in our hospital between January 2016 and August 2019. Clinical and laboratory variables at diagnosis, rates of complete remission(CR) at 6 months, defined as Birmingham Vasculitis Activity Score (BVAS)=0 and prednisone 7.5 mg/day, AAV relapse at 12 months, and adverse effects were investigated. Results: Of 40 patients, mean age was 73.5±9.6 years (6 males and 34 females). Diagnosis of MPA and GPA were 30 cases and 10 cases, respectively. 37 cases (93%) were positive for MPO-ANCA. Treatment regimen was determined by attending physician. Baseline characteristic of each group (RTX group and CY group) are shown in Table1. Baseline charactor, disease activity, organ involvement, and the proportion of patients with relapsing disease were similar in the two treatment groups. At 6 months, there was no difference of remission rate between two groups (RTX: CY = 62%: 44%, p=0.35) (Figure 1 ). However, mean PSL dosage at 3 months was significantly lower in RTX group (10.0±4.6mg/day) as compared to CY group (15.8±9.5mg/day; p=0.025) (Figure 2 ). At 12 months, 1 case in CY group and no case in RTX group had relapse. Adverse effects through 12 months are shown in Table 2 . 8 infections (30%) in CY group and 7 infections (35%) occurred in RTX group (p=0.64), respectively. 1 case in RTX group had died due to renal failure. Conclusion: We indicated that PSL was tapered more rapidly in RTX group, although there was no difference of remission rate at 6 months and infection at 12 months between RTX and CY therapy. Therefore, remission induction therapy with RTX might be more safety for elderly Japanese AAV patients. References: [1]Little MA, Nightingale P, Verburgh CA, Hauser T, et al. Ann Rheum Dis 2010; 69:1036–1043. Disclosure of Interests: None declared